วาทกรรมวิเคราะห์เปรียบเทียบคณะรสช. ปี 2534 และ คณะคปค. ปี 2549 - เพชรรัชต์ กันยาบาล (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The objectives of this qualitative research on comparative analysis of discursive practices between the 1991 National Peace Keeping Council and the 2006 Council of Democratic Reform of the Constitutional Monarchy are to do comparative analysis on enforcements during the coup period which brought upon the discursive practices as well as intensive observation of the two council’s leaders and their teams which concentrated on 4 main relevant events. 1. The cause of the Coup as well as timeline of the Coup day 2. Selection of the Board of property inspection 3. New government Constitutional Law and Prime Minister by appointment or by selection 4. Contradiction between the Thai government and the citizens as well as the inherit of power The research came out with a conclusion that the discursive practices of the two Councils took place under a similar circumstances but somewhat different in certain criteria. Therefore, the discourse of the two Councils were different regarding to the situation, but nevertheless, shared the same scope which was to intensify the goodness of oneself and the badness of the opponent, moreover downplaying the badness of oneself while submerging the goodness of the opponent.